Securing Forest Tenure Rights for Rural Development : Forest Tenure Assessment Tool and User Guide - World Bank (World Bank, Washington, DC, 2021)
The forest tenure assessment tool (FTAT) and user guide consists of an integrated set of methodologies and guidelines for assessing both why it is important to secure community-based forest tenure in a specific national or sub-national context, and what needs to be done to strengthen forest tenure in that context. It is a companion piece to the analytical framework (AF), developed during phase one of the securing forest tenure rights for rural development initiative. The AF highlights the relevance of secure community-based forest tenure to sustainable development goals (SDG), and presents a set of key elements derived from evidence and best practice in securing community forest tenure. Community-based forest tenure is important because tenure security is key in achieving a range of SDGs. One part of the assessment methodology presented asks, why forest tenure reform? It focuses on consolidating country-specific evidence of the linkages between community-based forest tenure security and several, particularly relevant SDG. The methodology involves exploring opportunities to achieve development goals by strengthening tenure security, as well as risks to the achievement of development outcomes where tenure is insecure. This part of the methodology is aimed at developing policy rationales for dialogue with high-level decision-makers in governments and the World Bank. A second part of the methodology presented here examines how to secure collective forest tenure and focuses on assessing the current status of community tenure security in forest areas. The objective is to enable participatory diagnostic assessments of the strengths and weaknesses of current land and forest tenure frameworks, capacities, and implementation processes. This assessment tool is designed for anyone interested in understanding and strengthening community-based tenure security in forest landscapes in any country or region. The following sections provide an overview of the two part assessment methodology for understanding the why and how dimensions of community-based forest tenure in section two; step-by-step process guidelines for conducting assessments in section three; a final section that identifies five broad categories of Bank products and services that can benefit from the FTAT and a range of modalities of implementation that vary in cost and duration in section four.